ANALISIS STRATEGI PEMASARAN TOMORO COFFEE DALAM MENINGKATKAN LOYALITAS PELANGGAN - Mutia Nurul Apriza; Mimi Kurnia Nengsih (UM. Bengkulu, 2026)
This study aims to determine the marketing strategy implemented by Tomoro Coffee in increasing customer loyalty at Tomoro Coffee Ruko Mahakam, Bengkulu City using the 7P marketing mix approach (product, price, place, promotion, people, process, and physical evidence). This research is a qualitative study with a descriptive approach. The informants were determined using purposive sampling technique. Data collection methods were conducted through in-depth interviews, observation, and documentation. Meanwhile, the data analysis technique used an interactive analysis model which includes data reduction, data presentation, and drawing conclusions.The results of this study indicate Tomoro Coffee has implemented an integrated marketing strategy based on the 7P marketing mix to build customer loyalty. The product strategy is implemented through consistent coffee taste quality and innovative menu variations. The price strategy is implemented by setting competitive prices and in accordance with customer value perceptions. The place strategy is supported by a strategic and easily accessible location. The promotion strategy is carried out through digital media, especially social media and online ordering applications. In addition, the elements of people, process, and physical evidence also play an important role in creating a positive experience for customers. The implementation of this marketing strategy contributes to building customer satisfaction, trust, and experience which ultimately encourages customer loyalty at Tomoro Coffee Ruko Mahakam, Bengkulu City. Keywords: marketing strategy, 7P marketing mix, customer loyalty, coffee shop, Tomoro Coffee.